Petrophysical Properties of Mauddud Formation in Selected Wells in Al-Ahdab Oil Field, Middle Iraq - Hameed, Ali S.; Faisal, Rasha F. (Iraqi Journal of Science, 2023)
This paper aims to calculate the petrophysical properties in the Al-Ahdab field in the middle of Iraq within the Mauddud Formation. This study was based on the information available from well logs. The interactive petrophysical software IP (V4.5)  was used to calculate the porosity, hydrocarbon saturation and shale volume, divide the formation into reservoir units and buffer units, and evaluate these units in each well. The Mauddud was divided into five units, two of them were considered good reservoirs having good petrophysical properties (high porosity, Low water saturation, and low shale volume). The other three are not reservoirs because of poor petrophysical properties.